(3eSfO GHf QGghjgs - (3GHf QGghjI , ESMGb Hf EHQGgje Hf eNdO GdMfXdj, CHh jYbhH,J (B238 (3g` s
(3ChdgG (B:s
(3Yf QShd Gddg Udi Gddg Ydjg hSde CNHQfG GdebeQ Hf SdjeGf bGd SeYJ CjhH jMOK Yf CHj bdGHg Yf CHj gQjQI s
(3BNQgG (B:s
(3Yf YcQeI Yf Ydi Yf QShd Gddg Udi Gddg Ydjg hSde BNQ GdeLdO GdQGHY ef cJGH GdeSfO dCHj jYbhH s
(3Vef eLehY , JQJjHgG (B: (3GdQGHYs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B292 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B228s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1678s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MOjK (B454) s
Keywords: (3GdMOjK h GdeUWdMs